Edward Donald Evans. (30th November 2019) - Jones, Ronald S.; Tobin, Janet
Abstract : A popular and competent clinician who was keen to share his knowledge. His experiences during the 1967 foot‐and‐mouth disease outbreak led him to join the state vet service, where he gained expertise investigating diseases in farm animals.